Pharmaceutical Discharge Management: Implementation in Swiss Hospitals Compared to International Guidelines - Studer, Helene (Pharmacy (Basel), 2021)
Readmissions to the hospital are frequent after hospital discharge. Pharmacist-led interventions have been shown to reduce readmissions. The objective of this study was to describe pharmacist-led interventions to support patients’ medication management at hospital discharge in Switzerland and to compare them to international guidelines. We conducted a national online survey among chief hospital pharmacists focusing on medication management at hospital discharge. To put our findings in perspective, Cochrane reviews and guidelines were searched for summarised evidence and recommendations on interventions. Based on answers in the survey, hospitals with implemented models to support patients at discharge were selected for in-depth interviews. In semi-structured interviews, they were asked to describe pharmacists’ involvement in the patients’ pathway throughout the hospital stay. In Swiss hospitals (n = 44 survey participants), interventions to support patients at discharge were frequently implemented, mostly “patient education” (n = 40) and “communication to primary care provider” (n = 34). These interventions were commonly recommended in guidelines. Overall, pharmacists were rarely involved in the interventions on a regular basis. When pharmacists were involved, the services were provided by hospital pharmacies or collaborating community pharmacies. In conclusion, interventions recommended in guidelines were frequently implemented in Swiss hospitals, however pharmacists were rarely involved.